The theory of trade and protection - Travis, William Penfield (Cambridge, Mass. : Harvard University Press, 1964)
This is a book on Theoretical Economics, considered as the logical analysis of an economic system of private enterprise, without any inclusion of reference to institutional controls.
Includes bibliographical footnotes and index.
osc 12/07/2018
Loans
Keywords: Protectionism; Free trade; Commercial policy